Analyze the heterogeneity structure of two sets of different spatial data with prediction - Ghanim Al-Hasoud; Mohammed Qasim (College of Education for Pure Sciences, 2007)
AbstractThis research tackles the analysis of spatial covariance structure for two different spatial data sets which involve the crome ore and copper ore respectively, where crome ore lies in a regular lattice and the copper ore lies in an irregular lattice. The fitted Varigoram function to the crome ore is appeared to be the spherical model while the fitted one to the copper ore is appeared to be the De Wijsian model, the De Wijsian model is characterized to have infinite variance and this can be seen in figures that are obtain in this work. Finally, the elementary Krigins is carried to both ores and the results are encouraging. الخلاصة یهدف هذا البحث إلى تحلیل بنیة التغایر المکانی لمجموعتین مختلفتین من البیانات المکانیة وتمثل المجموعة الأولى بیانات لمعدن الکروم (cr) والتی تقع فی شبکة منتظمة (Regular Lattice) . أما بیانات المجموعة الثانیة فهی بیانات لمعدن النحاس (cu) والتی تقع فی شبکة غیر منتظمة (Irregular Lattice) ، وتم توفیق دالة الڤاریوکرام لمعدن الکروم (cr) والذی تبین أنه موافق للنموذج الکروی (Spherical model) بینما المعدن الثانی معدن النحاس (cu) موافق لنموذج دیڤزین (De wijsian model) والنموذج الأخیر یتمیز بکون تباینه غیر محدد وهذا ما تظهره الأشکال التی زودت بهذا البحث وکذلک تم إجراء تنبؤ کریگنک الاعتیادی على البیانات وکانت النتائج مشجعة .